2015
DOI: 10.1111/pai.12315
|View full text |Cite
|
Sign up to set email alerts
|

Association between childhood atopic dermatitis, malnutrition, and low bone mineral density: A US population‐based study

Abstract: Children with AD have lower BMD, particularly those with malnutrition and Hispanic ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Atopic disease has been shown to be associated with several different comorbid conditions, many of which are known to increase the risk for anemia. The chronic inflammation present in atopic disease, use of systemic immunosuppressant medications, increased incidence of malnutrition 17,21,22 and/or obesity, [6][7][8] and increased use of alternative medicines 23 are examples of such comorbidities. Nevertheless, there is a paucity of data examining the association between atopic disease and anemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Atopic disease has been shown to be associated with several different comorbid conditions, many of which are known to increase the risk for anemia. The chronic inflammation present in atopic disease, use of systemic immunosuppressant medications, increased incidence of malnutrition 17,21,22 and/or obesity, [6][7][8] and increased use of alternative medicines 23 are examples of such comorbidities. Nevertheless, there is a paucity of data examining the association between atopic disease and anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the underlying mechanisms, awareness of the association between atopic disease and anemia is important. Physicians who care for children with atopic disease should be aware that fatigue may be related to unrecog- 17,21,22,24 and that patients with atopic disease are at an increased risk for low bone mineral density 17,18,25 and vitamin D deficiency. 26,27 Iron deficiency anemia is estimated to affect 3% of US children aged 1 to 2 years and is the most common type of microcytic anemia in childhood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we did not find an association between SCORAD and 25(OH)D or iPTH, it is interesting to include iPTH in studies like the one that this letter is commenting on . Silverberg found that children with AD had no difference in PTH from controls, but AD severity was not assessed. We have not found studies investigating the action of PTH on the atopic skin barrier.…”
mentioning
confidence: 64%